Overview of Young Mothers’ Readiness in Giving Exclusive Breastfeeding in the Ajibata District, Toba Regency, North Sumatra Province - Ni Nyoman Budiani; Mikawati; Kusmiyati; Sesca Diana Solang; Loso Judijanto (Postgraduate, University of Mataram, 2024)
Mothers have an important role in the development of children's growth and development from an early age. Child development will take place optimally with exclusive breastfeeding from the mother. However, field data shows that young mothers still do not have knowledge and understanding of the importance of exclusive breastfeeding for children. This study aims to determine the readiness of young mothers in exclusive breastfeeding in Ajibata District, Toba Regency, North Sumatra Province. This study used descriptive research with a cross sectional design conducted at the Ajibata Health Center. The research sample used quota sampling which amounted to 30 people with a questionnaire as a research instrument. The results showed that the picture of readiness to provide exclusive breastfeeding in Ajibata District was influenced by the education level of young mothers dominated by high school graduates totaling 23 people and young mothers who were ready to provide exclusive breastfeeding both physically and mentally totaling 23 people.